2008
DOI: 10.1136/bjo.2008.150995
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of complement factor H (Y402H) and treatment of exudative age-related macular degeneration with ranibizumab

Abstract: Aims To determine whether complement factor H (CFH) genotypes have a pharmacogenetic effect on the treatment of exudative age-related macular degeneration (AMD) with ranibizumab. Methods A retrospective study of 156 patients with exudative AMD treated with intravitreal ranibizumab monotherapy was conducted. AMD phenotypes were characterized by clinical examination, visual acuity, fundus photography, fluorescein angiography, and injection timing. Patients received intravitreal ranibizumab injections as part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
93
2
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 15 publications
4
93
2
4
Order By: Relevance
“…(62,67) Recently, two studies have demonstrated the association between gene polymorphisms and the response to intravitreal injections of the antivascular endothelial growth factor (anti-VEGF) agents bevacizumab and ranibizumab. (69,70) Brantley et al conducted a study in which eighty-six patients with exudative AMD undergoing treatment with 1.25 mg intravitreal bevacizumab in one eye were enrolled. Intravitreal injections were performed at 6-week intervals until there was no longer evidence of active neovascularization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(62,67) Recently, two studies have demonstrated the association between gene polymorphisms and the response to intravitreal injections of the antivascular endothelial growth factor (anti-VEGF) agents bevacizumab and ranibizumab. (69,70) Brantley et al conducted a study in which eighty-six patients with exudative AMD undergoing treatment with 1.25 mg intravitreal bevacizumab in one eye were enrolled. Intravitreal injections were performed at 6-week intervals until there was no longer evidence of active neovascularization.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, over 9 months, patients with both risk alleles received approximately 1 more intravitreal injection. (70) There is only one study with a large number of patients that addresses the preventive treatment of dry AMD related to the genetic polymorphisms. As we can observe, the majority of published articles about the therapeutic response of exudative AMD are related the photodynamic therapy and many of them are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In the light of the recent reports, it can be considered that the potential risk factors for non-responsiveness to anti-VEGF agent in the treatment of n-AMD are an initial lesion with subfoveal fibrosis or atrophy in retina pigment epithelium and photoreceptors, lesion in large size, type 1 choroidal neovascularization, serous pigment epithelium detachment (PED), haemorrhagic PED, fibrovascular PED, polypoidal choroidal vasculopathy, foveal scarring and vitreomacular traction, outer retinal tubulation, cystoid degeneration in outer retina, genetic disposition or an anti-VEGF resistance [Table 1, 13-22]. Table 1: The possible risk factors for non-responsiveness to anti-VEGF agents in the patients with nAMD [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Editorialmentioning
confidence: 99%
“…[2][3][4][5] Pivotal and post-licensing studies of PDT and antiangiogenic agents have suggested that lesion position and type influences the response to treatment. 3,6,7 Healthcare providers who are faced with expensive new therapies may seek to limit treatment to specific clinical groups who were shown to experience maximum benefit or to patients who fulfil the eligibility criteria that were set in the key licensing trials. Examples of this include the guidance that has been issued by the National Institute for Clinical Excellence (NICE) in the United Kingdom, limiting PDT treatment to specific angiographic subtypes and more recently by issuing guidance on eligibility for treatment with antiangiogenic agents.…”
Section: Introductionmentioning
confidence: 99%